ANIMAL AND VEGETABLE LIPID SOLUTION TEST IN IDENTIFYING FATTY ACID HYDROLYSIS REACTIONS - sridelfi kurniyati mahmud (Jurnal Ilmiah dr. Aloei Saboe, 2023)
This study aims to determine the solubility of animal and vegetable lipids, and can determine the saponification reaction in fats and determine the amount of saponification and determine the unsaturation of fatty acids through the determination of the iodine value. The research method used is a laboratory experimental method to obtain result data. The results showed that in the fat solubility test experiment, it was seen that cooking oil could not dissolve in all solutions because distilled water was water so oil which was insoluble in water could not dissolve in the solvent. Saponification reaction test: Oil dissolves when a solvent or alcohol reagent is added. The number of saponification with the results obtained that do not match the results with the experiment is because an error occurred during the practicum so that the color that should appear, which is pink, turns cloudy.